Whole-Genome Methylation Analysis Revealed ART-Specific DNA Methylation Pattern of Neuro- and Immune-System Pathways in Chinese Human Neonates - Liu, Zongzhi; Chen, Wei; Zhang, Zilong; Wang, Junyun; Yang, Yi-Kun; Hai, Luo; Wei, Yuan; Qiao, Jie; Sun, Yingli (Frontiers in Genetics, 2021)
DNA methylation of human offspring can change due to the use of assisted reproductive technology (ART) , in order to find the differentially methylated regions（DMRs） in ART newborns, cord blood maternal cell contamination and parent DNA methylation backgroud, which will add noise to the real difference, must be removed. We analyzed newborns heel blood from 6 families to identify the DMRs between ART and natural pregnancy newborns, and the genetic model of methylation was explored，meanwhile we analyzed 32 umbilical cord blood of infants with ARTs and normal pregnancy to comfirm which differences are consistent with cord blood data. The DNA methylation level was lower in ART-assisted offspring at the whole genome-wide level. differentially methylated sites (DMSs) , DMRs and cord blood differentially expressed genes(DEGs) are enriched in the important pathways of the immune system and nervous system, the genetic patterns of DNA methylation can be changed in ART group. 3 imprinted genes and 28 housekeeping genes which involved in the nervous and immune systems were significant difference between the two groups, 6 of them can be detected both in heel blood and cord blood. We concluded that there is ART-specific DNA methylation pattern involved in neuro- and immnue system pathways of human ART neonates, providing an epigenetic basis for the potential long-term health risks in ART-conceived neonates.